2018
DOI: 10.30871/jama.v2i1.727
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Financial Ratio on Financial Distress in Predicting Bankruptcy

Abstract: This study was conducted to investigate Financial Distress in mining companies listed on the Indonesian Stock Exchange (BEI) during the 2011-2014 period using the Altman Z-Score Modification. Total sample that gathered from mining companies is 119 companies, analytical techniques used in this study is the Altman Z-score that consists of four ratios, which are the Net Working Capital to Total Assets (X1), Retained Earnings to Total Assets (X2), Earnings Before Interest and Tax to Total asset (X3), Market Value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 0 publications
2
13
1
5
Order By: Relevance
“…High liquidity indicates a lot of unbalanced cash in an effort to generate profits, so that the profit earned becomes low. This result supports the findings of previous research done by Mas'ud and Srengga [11], and Supriyanto and Darmawan [16], but does not confirm the findings of Tan [14], Restianti and Agustina [9], and Lumbantobing [15] Lumbantobing [17] which revealed that profitability ratio significant negatively effects on the condition of financial distress.…”
Section: Earning Ratiocontrasting
confidence: 83%
“…High liquidity indicates a lot of unbalanced cash in an effort to generate profits, so that the profit earned becomes low. This result supports the findings of previous research done by Mas'ud and Srengga [11], and Supriyanto and Darmawan [16], but does not confirm the findings of Tan [14], Restianti and Agustina [9], and Lumbantobing [15] Lumbantobing [17] which revealed that profitability ratio significant negatively effects on the condition of financial distress.…”
Section: Earning Ratiocontrasting
confidence: 83%
“…It indicates that positive influence is showed by this ratio toward financial distress. These results are persistent with [7] research results stating that the ratio of EBITTA positively affect financial distress. This variable also has a significance value of 0.000 which affects financial distress with the very significant effect.…”
Section: 6the Effect Of Ebitta Ratio On Financial Distressmentioning
confidence: 79%
“…His research used four ratios in the Altman Z-Score modification with the research conclusions point out that the four ratios had a positive influence on financial distress. [7] also examined the effects of four ratios in the Altman Z-Score modification model on financial distress and resulted that this ratio positively affected financial distress. This research is expected to provide confirmation and accurate illustration of how the effect of ratio of the Altman model on financial distress.…”
Section: Introductionmentioning
confidence: 99%
“…The agency theory discusses the relationship between the manager (which is known as agent) and the shareholders (which is the capital provider to the company managed by the agents) (Supriyanto and Darmawan, 2018). This relationship is shaped by individualistic and opportunistic interests by both parties.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The aforementioned studies showed that consumer product companies in South East Asia are significantly affected by the financial crisis considering the decline in demand for non-essential goods. This current study adopts the purposive sampling technique where samples are determined based on certain criteria (Supriyanto and Darmawan, 2018). The cross section model is employed whereby more than one variable is collected at the same time.…”
Section: Sample Selectionmentioning
confidence: 99%